PENGARUH CASHLESS PAYMENT TERHADAP PERTUMBUHAN EKONOMI: STUDI KOMPARASI NEGARA MAJU DAN BERKEMBANG ANGGOTA G20 - Sitanggang, Maria Septiani; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2024)
The purpose of this study is to analyze the impact of cashless payments on economic growth in G20 countries. Additionally, a comparison of the impact of cashless payments in developed and developing countries is also analyzed. In this study, economic growth is used as the dependent variable, and transaction amounts of debit cards, credit cards, and electronic money are used as the independent variables. Data were collected from various databases for the period 2013-2021 covering a total of 19 countries divided into 10 developed countries and 9 developing countries that are members of the G20. The test results using the Generalized Method of Moments (GMM) dynamic panel found that all three variables have a significant effect in both developed and developing G20 member countries. Furthermore, the study found that the biggest influence of non-cash payments in developed countries is transactions using debit cards while in developing countries it is transactions using credit cards and electronic money. From these results, it was concluded that cashless payments have an impact on economic growth. It is hoped that these findings will provide new insights into cashless payments and their impact on economic growth.